Quadriceps strength asymmetry as predictor of ankle sprain in male volleyball players - Hadzic, V.; Sattler, T.; Pori, P.; Veselko, M.; Derviševic, E.; Sarabon, N.; Markovic, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Ankle sprain is the most common acute time-loss injury in volleyball and occurs mainly during landing from a jump. Therefore, we have evaluated the role of quadriceps strength and countermovement jump height on ankle sprain occurrence, as these intrinsic modifiable risk factors were not yet evaluated. We have also hypothesized that presence of quadriceps strength asymmetry could be a possible risk factor for ankle sprains in male volleyball players. METHODS: This was a prospective cohort study. Male volleyball players (N.=99) from Slovenian national league participated in the study. Before the start of the season, all participants completed a preseason questionnaire and underwent evaluation of vertical jump performance and bilateral isokinetic strength of the quadriceps (Q) and hamstrings (H). During the subsequent season the players reported acute time loss injuries because of ankle sprain through a weekly questionnaire. RESULTS: We have registered 19 ankle sprains during the season. Overall ankle sprain incidence was 0.41±0.24 per 1000 h. Previous ankle sprain (Odds Ratio: 0.86; 95% CI: 0.25-2.89, P=0.802) and jump height (1.05; 95% CI: 0.94-1.19, P=0.393) were not significant risk factors, while Q strength asymmetry was a significant predictor of an ankle sprain (Odds Ratio: 0.956; 95% CI: 0.919-0.995, P=0.026). Compared with the uninjured players, the injured players had higher right concentric Q strength, higher Q strength asymmetry, and lower concentric right H-Q strength ratio (all P<0.03). CONCLUSIONS: Our results suggest that excessive concentric strength of the right Q, which leads to low H-Q strength ratio, and high bilateral Q strength asymmetry in favor of the right side, could be associated with increased risk of ankle sprains in male volleyball.